Response of Scots Pine (Pinus sylvestris) to Warming Climate at Its Altitudinal Limit in Northernmost Subarctic Finland - Holtmeier, Friedrich-Karl; Broll, Gabrielle (ARCTIC, 2011)
The present study aims to contribute to a fine regional differentiation of Scots pine (Pinus sylvestris) response to climate change at its altitudinal margins in subarctic Finland north of 69˚ N (Utsjoki) and to find out whether a prompt establishment of new pines in response to climate change can be expected above the old pine tree limit in and above the mountain birch zone. In 10 sampling areas, distribution, site characteristics, and condition (damage degree, growth forms) of the new pines (pines that have become established since the mid 20th century) were checked in a zone 50 m to the left and right of our field routes. The field routes extended from the scattered birch forest to the treeless alpine zone and mountaintops and covered a total area of more than 4 km2. In total, 213 new pines were found. Tree height was measured and age estimated by counting the whorls. The degree of damage was estimated and then attributed to four damage classes. Pine establishment was most successful during the 1970s and up until the end of the last century. Pines younger than 10 years are rare (< 3%) in the study areas, with one exception (about 8%). Pine recruitment is comparatively intense in close proximity to old pines in the birch forest while it is sporadic within the scattered birch stands at higher elevations and in the alpine tundra. More than 80% of the new pines show disturbed growth forms due to frequent winter injury, reindeer, and moose. About 66% exhibit severe damage, and 15% have already died. On windswept terrain, microsite facilitation is essential for pine establishment. Lack of local seed sources and severe site conditions at high elevations have probably delayed pine altitudinal advance. New pine generations may become effective seed sources speeding up pine advance beyond the present seed trees. In view of the high proportions of severely damaged and dead new pines, we do not expect that climatic warming will bring about a rapid advance of the pine tree limit. La présente étude vise à contribuer à ...